OpenStack object storage (Swift) essentials : design, implement, and successfully manage your cloud storage using OpenStack Swift /: design, implement, and successfully manage your cloud storage using OpenStack Swift. (2015) - Kapadia, Amar; Varma, Sreedhar; Rajana, Kris
No abstract available